2013
DOI: 10.1111/jipb.12110
|View full text |Cite
|
Sign up to set email alerts
|

Iron deprivation results in a rapid but not sustained increase of the expression of genes involved in iron metabolism and sulfate uptake in tomato (Solanum lycopersicum L.) seedlings

Abstract: Characterization of the relationship between sulfur and iron in both Strategy I and Strategy II plants, has proven that low sulfur availability often limits plant capability to cope with iron shortage. Here it was investigated whether the adaptation to iron deficiency in tomato (Solanum lycopersicum L.) plants was associated with an increased root sulfate uptake and translocation capacity, and modified dynamics of total sulfur and thiols accumulation between roots and shoots. Most of the tomato sulfate transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 60 publications
2
41
0
Order By: Relevance
“…The expression of both SlFRO1 and SlIRT1 genes is controlled by the basic helix-loop-helix (bHLH) transcription factor SlFER. Their expression was detected only in roots under all nutritional conditions analyzed, and as previously described (Paolacci et al, 2014), the relative amounts of their transcripts in roots of control plants were markedly different (Fig. 4).…”
Section: Transcriptional Analysis Of Fe Stress-related Genessupporting
confidence: 80%
See 3 more Smart Citations
“…The expression of both SlFRO1 and SlIRT1 genes is controlled by the basic helix-loop-helix (bHLH) transcription factor SlFER. Their expression was detected only in roots under all nutritional conditions analyzed, and as previously described (Paolacci et al, 2014), the relative amounts of their transcripts in roots of control plants were markedly different (Fig. 4).…”
Section: Transcriptional Analysis Of Fe Stress-related Genessupporting
confidence: 80%
“…The expression of genes involved in Fe homeostasis (SlFRO1, SlIRT1, and SlFER) and coding for STs of groups 1, 2, and 4 (SlST1.1, SlST1.2, SlST2.1, SlST2.2, and SlST4.1) were analyzed by qRT-PCR as described in Paolacci et al, 2014. In particular, qRT-PCR analyses were performed using an Mx3000PTM Real-Time PCR System with Brilliant SYBR Green QPCR Master Mix (STRA-TAGENE) according to manufacturer's protocols in 25-mL reaction volumes containing 1 mL of each 5-fold diluted cDNA and 150 nM forward and reverse primers (reported for each analyzed gene in Paolacci et al, [2014]).…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is of interest to place our findings in the context of studies that have reported on the general effects of Fe deficiency on chlorophyll synthesis and photosynthesis that have been well documented in the literature (Spiller and Terry, 1980;Andaluz et al, 2006;Nishio and Terry, 1983;Nishio et al, 1985;Sharma, 2007;Timperio et al, 2007;Laganowski et al, 2009;Msilini et al, 2011;Ciaffi et al, 2013;Paolacci et al, 2014;Rodríguez-Celma et al, 2013). Some studies on Fe depletion in plants reported that PSI was the major target of Fe deficiency (Nishio et al, 1985;Timperio et al, 2007), whereas we saw a major effect on the cytochromeb 6 f complex and less on PSI.…”
Section: Fe Sparing In Chloroplasts Targets Abundant Fe Proteinsmentioning
confidence: 46%